Personalized Graduate Medical Education and the Global Surgeon: Training for Resource-Limited Settings. (15th December 2020) - Davis, Rachel W.; Sherif, Youmna A.; Vu, Megan Thuy; Shilstone, Holly; Scott, Bradford; Olutoye, Oluyinka O.; Hollier, Larry; Nuchtern, Jed; Rosengart, Todd K.
Abstract : Problem: The World Health Organization and the World Bank have identified improvement in access to surgical care as an urgent global health challenge and a cost-effective investment in public health. However, trainees in standard U.S. general surgery programs do not have adequate exposure to the procedures, technical skills, and foundational knowledge essential for providing surgical care in resource-limited settings. Approach: The Michael E. DeBakey Department of Surgery at Baylor College of Medicine (BCM) created a 7-year global surgery track within its general surgery residency in 2014. Individualized rotations equip residents with the necessary skills, knowledge, and experience to operate in regions with low surgeon density and develop sustainable surgical infrastructures. BCM provides a formal, integrated global surgery curriculum—including 2 years dedicated to global surgery—with surgical specialty rotations in domestic and international settings. Residents tailor their individual experience to the needs of their future clinical practice, region of interest, and surgical specialty. Outcomes: There have been 4 major outcomes of the BCM global surgery track: (1) increased exposure for trainees to a broad range of surgeries critical in resource-limited settings, (2) meaningful international partnerships, (3) contributions to global surgery scholarship, and (4) establishment of sustainable global surgery activities. Next Steps: To better facilitate access to safe, timely, and affordable surgical care worldwide, global surgeons should pursue expertise in topics not currently included in U.S. general surgical curricula, such as setting-specific technical skills, capacity building, and organizational collaboration. Future evaluations of the BCM global surgery track will assess the effect of individualized education on trainees' professional identities, clinical practices, academic pursuits, global surgery leadership preparedness, and comfort with technical skills not encompassed in general surgery programs. Increasing availability of quality global surgery training programs would provide a critical next step toward contributing to the delivery of safe surgical care worldwide.